Peran Remaja dalam Pemberdayaan Masjid di Desa Payarengas Kecamatan Hinai Kabupaten Langkat Sumatera Utara - Nadya Nurcahyani; Khairunisa Pratiwi; Barratun Nisra Hasra; Devi Mawarni; Putri Nabila Yuhanda Hutabarat (MODELING: Jurnal Program Studi PGMI, 2023)
The mosque is a place of worship for Muslims and is used as a meeting place for Muslims to worship. Studying and deepening Islam to foster a love for places of worship and follow Islam. The mosque is the center of Islamic activity. The mosque functions as a place of worship for Muslims, a center for knowledge, worship, creating ukhuwah Islamiyah and fostering the people. Adolescence is a period of human development, namely the transition from childhood to adulthood where there are biological, psychological, and social changes. Adolescence is often defined as a transitional period between childhood to adulthood, or adolescence, or someone who exhibits certain behaviors as unruly, easily triggered emotions, etc. This provides an opportunity for members to develop according to their talents and creativity under the guidance of the mosque manager/Tamir. The main goal of the Mosque Youth Organization is to invite the community, especially youth, to join together in this mosque youth organization to be active in mosques having syar`i activities such as regular recitations, seminars, and positive events that all other events at the mosque will have. In addition, the Mosque Youth Organization will also try to point in a direction that is truly in accordance with the Shari'a through continuous assistance to its members. Teenagers need an Islamic environment, so the mosque youth is a way to fortify themselves from something negative. The organizational process to support the implementation of the Ta'mir Mosque activities. The background of the initial problems and obstacles for the youth of the Nurul Hikmah mosque was the Covid-19 pandemic, where the pandemic hit all over the world which began in 2019 until now.